Characterization of soil macrofauna in grain production systems in the Southeastern state of Piauí, Brazil - Santos, Djavan Pinheiro dos; Santos, Glenio Guimarães; Santos, Isis Lima dos; Schossler, Thiago Rodrigo; Niva, Cintia Carla; Marchao, Robelio Leandro (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to characterize the edaphic macrofauna in agricultural grain production systems under no-tillage and conventional tillage, in the Shoutheastern state of Piauí, in the Matopiba region, Brazil. Soil samples were taken from the 0.0–0.1, 0.1–0.2, and 0.2–0.3-m layers, with litter, in areas predominantly cropped with corn and soybean, under conventional and no-tillage systems, in soils with different textures. Fragments of native vegetation in adjacent areas were used as a reference. The edaphic macrofauna in the different land uses was identified down to family level, and the families were grouped according to their ecological functions. The most abundant groups in the sampled areas were Isoptera, Hymenoptera, and Coleoptera, the latter with the highest number of families. Principal component analysis revealed that the functional groups geophages/bioturbators, phytophages/pests, and predators/parasites were associated with clayey-silty soils, and detritivores/decomposers with sandy soils. Soil management systems change the community structure of edaphic macroinvertebrates in comparison with the natural Cerrado condition. No-tillage system promotes greater abundance and species richness than conventional tillage, and minimizes the impact of agricultural systems on edaphic macrofauna biodiversity.